Benign tumoral melanosis of a cervical lymph node in a child. (May 2020) - Boscoe, Elizabeth F.; Hararah, Mohammad K.; Lovell, Mark; Kelley, Peggy
Abstract: We present a pediatric case of benign tumoral melanosis in a cervical lymph node arising from congenital pigmented lesions of the anterior neck. This is the first reported pediatric case not associated with regressed melanoma or trauma. Tumoral melanosis is a rare phenomenon which describes a pigmented lesion like melanoma; however, histology demonstrates melanin-laden macrophages without malignant cells. In the few reported cases, tumoral melanosis has arisen in the skin or lymph node and associated with a regressed melanoma, pigmented basal cell carcinoma or mycosis fungoides. We discuss the pathology of this disease process, and the work up in a pediatric patient.